(untitled) (The Journal of Psychology and Sociology, 2019)
This article discusses the problems of the emotional sphere of University students. Personal and psychological characteristics of students were compiled; materials were presented on the difficulties encountered in the process of studying at the university and their influence on emotions. In connection with the age characteristics of the students, psychological changes were described, their adaptation to the new environment, the motives for getting education, their anxiety and fear of exams, the revelation of the emotional difficulties encountered by firstyear students, and problems with stress. Based on the analysis of foreign research on the problem of emotions, information on emotional changes and their role in the psychology of the personality has been taken as a theory. The content aspects of emotionality include perspectives and situations of particular importance to the subject. The qualitative properties of emotionality are characterized by the attitude of the individual to the phenomena of the external world. In accordance with the conclusions, the students were studied their emotional sphere by diagnostic techniques and further taken as the basis of correctional and developmental work with identified emotional difficulties. As a result of a comparative analysis of students’ emotional sphere, it was revealed that the emotional sphere of fourthyear students is harmoniously developed, students support their emotions and can in any degree control themselves in various life situations, which is the key to the success of a higher educational institution in providing psychological state students in the learning process. Analyzing the psychological sphere of students of higher educational institutions, at a given age period, a special place is occupied by the motivation for the future profession, it is theoretically formulated that students have positive emotions, as well as the ability to recognize and manage it, communicate with friends. Key words: emotions, emotional sphere, emotional experiences, feelings, stress, anxiety, emotional distance.